2012
DOI: 10.1074/jbc.m112.355206
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 Protein Deacetylates Isocitrate Dehydrogenase 2 (IDH2) and Regulates Mitochondrial Redox Status

Abstract: Background: NAD ϩ -dependent deacetylase SIRT3 is essential for the prevention of age-related hearing loss during caloric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
300
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(320 citation statements)
references
References 53 publications
(55 reference statements)
18
300
2
Order By: Relevance
“…Keratinocytes-SIRT3 acts through several targets to both reduce superoxide production and enhance the oxidative stress response and detoxification mechanisms (8,(11)(12)(13)(14)(15)(16)(17). Consistent with the repression of mitochondrial oxidative stress by SIRT3, mitochondrial superoxide levels decreased in SIRT3-overexpressing keratinocytes (Fig.…”
Section: Sirt3 Modulates Mitochondrial Superoxide Levels Insupporting
confidence: 62%
See 2 more Smart Citations
“…Keratinocytes-SIRT3 acts through several targets to both reduce superoxide production and enhance the oxidative stress response and detoxification mechanisms (8,(11)(12)(13)(14)(15)(16)(17). Consistent with the repression of mitochondrial oxidative stress by SIRT3, mitochondrial superoxide levels decreased in SIRT3-overexpressing keratinocytes (Fig.…”
Section: Sirt3 Modulates Mitochondrial Superoxide Levels Insupporting
confidence: 62%
“…Decreased availability of the sirtuin co-substrate NAD ϩ may lead to decreased SIRT3 activity in keratinocytes during differentiation. Given the well established role of SIRT3 as a regulator of mitochondrial oxidative stress (8,(11)(12)(13)(14)(15)(16)(17)(18), mitochondrial superoxide levels increased in both primary and immortalized keratinocytes with differentiation. We identified SIRT3 as a key regulator of this phenotype; constitutive SIRT3 deficiency resulted in increased mitochondrial superoxide levels, whereas constitutive SIRT3 expression reduced mitochondrial ROS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite a likely role for increased ROS production, it is not possible from the present study to determine whether impaired insulin secretion following SIRT3 knockdown occurred as a result of a primary defect in insulin secretion or as a consequence of increased beta cell apoptosis. The precise mechanisms governing increased ROS production in INS1 cells are unclear; however, in different tissues, SIRT3 has been reported to alter the acetylation status of a number of proteins linked to ROS production [20,23,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies showed that SIRT3 regulates mitochondrial biogenesis, and it is correlated with the expression of genes related to mitochondrial function, including PGC1α and UCP1 (Kong et al, 2010;Shi et al, 2005). Moreover, SIRT3 deacetylates isocitrate dehydrogenase 2 (IDH2) and regulates mitochondrial redox status (Yu et al, 2012). A recent study suggested that SIRT3 was regulated by nutrient excess.…”
Section: Sirt3mentioning
confidence: 99%